On casting clay specimens of bespoke shear strength and sensitivity for landslide modelling. Issue 4 (6th July 2020) - Kennedy, Ray; Siemens, Greg; Take, W. Andy
Abstract : Sensitive clay landslides are a geohazard often exhibiting flow-like retrogressive behaviour. Soils with high sensitivity experience significant strain softening − a key characteristic of these types of slope movements. In this paper, an experimental method using high early strength cement mixed with clay soil is investigated to cast repeatable samples of a bespoke shear strength and sensitivity while reducing specimen preparation time. The addition of cement bonds from hydration reactions was observed to encourage the development of a metastable soil structure with sufficiently high moisture content to exhibit both a high peak strength and a low remoulded strength. Various cement and water content mixtures were examined, with either kaolin clay or a naturally sensitive clay from Mud Creek, Ontario and Portland type 1 or type 3 cement. Undrained shear strength testing was measured with the Swedish fall cone and the miniature lab vane. Soil−cement mixtures developed shear strength of up to 60 kPa with sensitivities from 4 to 16 within a 7 d curing time. This paper reports lessons learned from the mixing, curing and testing of the sensitive material, as well as the results from a geotechnical centrifuge experiment examining retrogressive sensitive clay landslides.